INSTAGRAM SEBAGAI MEDIA PROMOSI TRIFTING UNTUK MENINGKATKAN JUMLAH PENGUNJUNG SAFE FESTIVAL DI CONVENTION HALL TIRTONADI - Sena, Aldhan Gradika; Suryo, Herning (Solidaritas, 2025)
The development of information and communication technology has made social media an inseparable part of everyday life. One of the most popular platforms in Indonesia is Instagram, which is used for various purposes, including product and event promotion. This study aims to examine Instagram as a promotional medium for the Save Festival at the Hal Tirtonadi Convention in increasing the number of visitors. Safe Festival only uses Instagram as the main promotional platform, with visual features such as interactive photos and videos and collaboration with local accounts to attract more visitors. Using a qualitative descriptive approach, this study collected data through observation, interviews, and documentation related to promotional activities on the @safeFestival Instagram account. The theories used by the author are promotion, marketing and social media. The results of the study indicate that the use of Instagram through visual uploads and reposting content can significantly increase the number of visitors. This study also supports the findings of previous studies on Instagram as a promotional medium with a focus on elements of visual interaction and targeted communication. Keywords: instagram, promotion, communication